1997
DOI: 10.1016/s0042-6989(97)00181-8
|View full text |Cite
|
Sign up to set email alerts
|

Visual sensitivity, blur and the sources of variability in the amplitude spectra of natural scenes

Abstract: A number of researchers have suggested that in order to understand the response properties of cells in the visual pathway, we must consider the statistical structure of the natural environment. In this paper, we focus on one aspect of that structure, namely, the correlational structure which is described by the amplitude or power spectra of natural scenes. We propose that the principle insight one gains from considering the image spectra is in understanding the relative sensitivity of cells tuned to different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
166
0
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 225 publications
(184 citation statements)
references
References 32 publications
16
166
0
2
Order By: Relevance
“…This is because structural information at the object level becomes finer in spatial terms as the object moves farther away, gradually slipping below the acuity limit of the observer. Also, in natural images, low spatial frequencies have much higher contrast levels, with the energy dropping off as a 1/f n function, where f is frequency and n is an exponent between about 1.1 and 2.2 (see, e.g., Field & Brady, 1997;Rainville & Kingdom, 1999). This means that obscuration that reduces contrast-such as glare or fog-will tend to affect the higher frequencies more.…”
Section: Discussionmentioning
confidence: 99%
“…This is because structural information at the object level becomes finer in spatial terms as the object moves farther away, gradually slipping below the acuity limit of the observer. Also, in natural images, low spatial frequencies have much higher contrast levels, with the energy dropping off as a 1/f n function, where f is frequency and n is an exponent between about 1.1 and 2.2 (see, e.g., Field & Brady, 1997;Rainville & Kingdom, 1999). This means that obscuration that reduces contrast-such as glare or fog-will tend to affect the higher frequencies more.…”
Section: Discussionmentioning
confidence: 99%
“…Boutet et al (2003) suggested, instead, that the middleband advantage might be due to the middle range of frequencies having sufficient amounts of both contrast and spatial information to be useful. The contrast in a natural image drops as 1/f n , where f is frequency and n is an exponent in the range of about 1-2 (Field & Brady, 1997). This means that the amount of contrast in a natural image is halved for every doubling of frequency.…”
Section: Discussionmentioning
confidence: 99%
“…The limitations of this research can be a subjective judgment of photographs, limited number of photographs examined, and some data accuracy in pixel counting. There have been also several other studies applied fractal dimension such as evaluating the texture discrimination (Keller et al, 1989) and observing luminance patterns in natural scenes (Field and Brady, 1997). We therefore suggest that these techniques may be useful for future studies of investigating visual quality assessment of understory vegetation cover by applying box-counting method and FD which may also elucidate spatial data acquisition techniques in the future.…”
Section: Figurementioning
confidence: 94%